2012
DOI: 10.2139/ssrn.1573308
|View full text |Cite
|
Sign up to set email alerts
|

The European Union, the Euro, and Equity Market Integration

Abstract: We use industry valuation differentials across European countries to study the impact of membership in the European Union as well as the Eurozone on both economic and financial integration. In integrated markets, discount rates and expected growth opportunities should be similar within one industry, irrespective of the country, implying narrowing valuation differentials as countries become more integrated. Our analysis of the 1990 to 2007 period shows that membership in the EU significantly lowered discount ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
19
0

Year Published

2013
2013
2015
2015

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 52 publications
0
19
0
Order By: Relevance
“…Estimating the balanced sample over the same period as the unbalanced sample leads to an insignificant EU effect (but significant Euro effect).22 Controlling for EU membership appears to improve the identification of the Euro effect, suggesting that our main results are robust even though we are unable to control for this effect.23 Bekaert et al (2013) use the divergence in valuations of industries between country pairs as a measure of equity market segmentation and found that EU membership reduces equity market segmentation between member countries independent of whether members have also adopted the Euro. Their results suggest that the Euro adoption as well as the anticipation of the Euro adoption has minimal effects on market integration.…”
mentioning
confidence: 87%
See 4 more Smart Citations
“…Estimating the balanced sample over the same period as the unbalanced sample leads to an insignificant EU effect (but significant Euro effect).22 Controlling for EU membership appears to improve the identification of the Euro effect, suggesting that our main results are robust even though we are unable to control for this effect.23 Bekaert et al (2013) use the divergence in valuations of industries between country pairs as a measure of equity market segmentation and found that EU membership reduces equity market segmentation between member countries independent of whether members have also adopted the Euro. Their results suggest that the Euro adoption as well as the anticipation of the Euro adoption has minimal effects on market integration.…”
mentioning
confidence: 87%
“…AlthoughBekaert et al (2013) suggest that membership in the EU has significantly influenced European stock market integration, we are unable to control for this effect with our methodology directly, but do so in a robustness test using panel regressions.16 Potential concerns are the stability of model parameters and the existence of structural changes during our sample period. Controlling for the volatility effect can potentially address these concerns since it represents a time-varying proxy for market conditions.…”
mentioning
confidence: 94%
See 3 more Smart Citations